Networks, Innovation and Knowledge Transfer in Tourism Industry: An Empirical Study of SMEs in Portugal - Lopes, João (2021)
The present study aims to investigate how commercialisation and knowledge transfer between the SMEs of the tourism sector and the higher education institutions (HEIs) are made, as well as to find out whether the SMEs of the tourism sector are part of tourism networks, and what their motivations are. We used a qualitative methodology, applying the triangulation method to eight SMEs and one HEI. The results indicate that the commercialisation and knowledge transfer between the SMEs and the HEIs are not effective. SMEs are part of regional networks of business innovation; however, they do not participate in R&D activities with HEIs. Some suggestions were made to SMEs, HEIs, and regional governments to speed up commercialisation and knowledge transfer in the tourism sector. We adapted the Triple Helix Model to the tourism sector, thus creating the “Triple Helix in the Tourism Context”. Only a few studies have researched knowledge commercialisation in the tourism sector, a gap that this article aims to compensate.